Antihyperglycaemic and Toxicological Evaluations of Extract and Fractions of Gynura procumbens Leaves - Khalid Algariri; Item Justin Atangwho; Kuong Yow Meng; Mohd Zaini Asmawi; Amirin Sadikun; Vikneswaran Murugaiyah (Tropical Life Sciences Research, 2014)
The acute and sub-chronic antihyperglycaemic activity, safety margin evaluations and chemical composition of ethanol extract (EE) and fractions of Gynura procumbens (GP) were studied. Streptozotocin (STZ)-induced diabetic rats (SDRs) and the Organisation for Economic Cooperation and Development (OECD) guidelines 425 and 407 were used in the antidiabetic and toxicity studies, respectively. Biochemical and haematological data obtained from both acute and sub-chronic procedures suggest that the extract is safe at the limit test dose (2000 mg/kg); thus, the oral lethal dose (LD50) exceeds 2000 mg/kg. The acceptable daily intake (ADI) was determined to be 700 mg/kg/day. In the acute antihyperglycaemic study, the n-butanol fraction (n-BF) was found to consistently lower glucose levels the most effectively, which was also demonstrated in the 14-day study. Not only did the n-BF show the highest dose-dependent glucose-lowering action (51.2% and 62.0% at 500 mg/kg and 1000 mg/kg, respectively), its effect was the closest to that of metformin (63.6%, p<0.05). The estimated amount of flavonoids in n-BF were 62.90% and 79.68% higher than the ethyl acetate fraction (EAF) and aqueous fraction (AF), respectively (p<0.05), with a corresponding value of 61.22% and 49.33% for phenolics (p<0.05). GP leaves have a no-observed-adverse-effect-level (NOAEL) and antihyperglycaemic activity corresponding to the high content of phenols and flavonoids. Therefore, GP leaves are a promising source of new antidiabetic natural products. Aktiviti antihiperglisemik akut dan subkronik, penilaian jurang keselamatan dan kandungan kimia ekstrak dan fraksi etanol (EE) Gynura procumbens (GP) telah dikaji. Tikus diabetik aruhan streptozotosin [(STZ) SDR] dan garis panduan Organisation for Economic Cooperation and Development (OECD) 425 dan 407 telah digunakan dalam kajian antidiabetik dan ketoksikan, masing-masing. Data biokimia dan hematologi yang diperolehi daripada kedua-dua prosedur akut dan sub-kronik mencadangkan bahawa ekstrak ini adalah selamat pada ujian had dos (2000 mg/kg); oleh itu, dos maut oral (LD50) ekstrak melebihi 2000 mg/kg. Pengambilan harian boleh terima (ADI) yang telah ditentukan ialah 700 mg/kg/hari. Dalam kajian antihiperglisemik akut, fraksi n-butanol (n-BF) didapati paling berkesan menurunkan paras glukosa secara konsisten, yang juga ditunjukkan dalam kajian 14 hari. Bukan sahaja n-BF menunjukkan penurunan glukosa bergantung kepada dos (51.2% dan 62.0% pada 500 mg/kg dan 1000 mg/kg, masingmasing) paling banyak, kesannya juga adalah yang paling mendekati metformin (63.6%, p<0.05). Jumlah flavonoid dalam n-BF dianggarkan sebanyak 62.90% dan 79.68% lebih tinggi daripada dalam fraksi etil asetat (EAF) dan fraksi akueus (AF), masing-masing (p<0.05) dan 61.22% dan 49.33% lebih tinggi bagi kandungan fenolik (p<0.05). Daun GP mempunyai paras dos tanpa kesan buruk kelihatan (NOAEL) dan aktiviti antihiperglisemik yang bersesuaian dengan kandungan fenol dan flavonoid yang tinggi. Oleh itu, daun GP menjanjikan sumber produk semula jadi antidiabetik baru.